2015
DOI: 10.15586/jkcvhl.2015.38
|View full text |Cite
|
Sign up to set email alerts
|

Revealing a Pre-neoplastic Renal Tubular Lesion by p-S6 Protein Immunohistochemistry after Rat Exposure to Aristolochic Acid

Abstract: Aristolochic acid (AA) has, in the last decade, become widely promoted as the cause of the Balkan endemic nephropathy and associated renal or urothelial tumours, although without substantial focal evidence of the quantitative dietary exposure via bread in specific households in hyperendemic villages. Occasional ethnobotanical use of Aristolochia clematitis might be a source of AA, and Pliocene lignite contamination of well-water is also a putative health risk factor. The aim of this study was two-fold: to veri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…Previous studies have suggested that environmental factors are able to induce deleterious effects within the cells through the activation of cellular receptors (Mnif et al 2007, Routledge et al 2000). It is important to note that the interactions between most of the environmental pollutants and their receptors are implicated in the regulation of molecular pathways involved in cancer progression, such as proliferation, metabolism of xenobiotics and apoptosis (Burz et al 2009, Duronio and Xiong 2013, Rushmore and Kong 2002. It is known that environmental molecules, such as TCDD, B[a]P, BPA and phthalates, have the ability to interact with the two types of cellular receptors: nuclear and membrane receptors (Delfosse et al 2014, Dong 2006, Wallace andRedinbo 2013).…”
Section: Receptors Targeted By Environmental Pollutantsmentioning
confidence: 99%
See 4 more Smart Citations
“…Previous studies have suggested that environmental factors are able to induce deleterious effects within the cells through the activation of cellular receptors (Mnif et al 2007, Routledge et al 2000). It is important to note that the interactions between most of the environmental pollutants and their receptors are implicated in the regulation of molecular pathways involved in cancer progression, such as proliferation, metabolism of xenobiotics and apoptosis (Burz et al 2009, Duronio and Xiong 2013, Rushmore and Kong 2002. It is known that environmental molecules, such as TCDD, B[a]P, BPA and phthalates, have the ability to interact with the two types of cellular receptors: nuclear and membrane receptors (Delfosse et al 2014, Dong 2006, Wallace andRedinbo 2013).…”
Section: Receptors Targeted By Environmental Pollutantsmentioning
confidence: 99%
“…Three major classes of membrane receptors exist: 1) the enzyme linked-receptors that lack intrinsic catalytic activity and dimerise after binding with their ligands, in order to activate downstream signal transductions pathways through one or more cytosolic protein-tyrosine kinase (i.e. human growth factor receptors) (Dudek 2007); 2) the channel-linked receptors (also called ligand-gated ion channels) where the ligand binding changes the conformation of the receptor; in this case, specific ions flow through the channel altering the electric potential across the membrane of the target cell (Absalom et al 2004); and 3) the G-protein coupled receptors (GPCRs).…”
Section: Membrane Receptorsmentioning
confidence: 99%
See 3 more Smart Citations